EARNINGS OF ONLINE MOTORCYCLE TAXI BIKERS OPERATING IN PALANGKA RAYA: (CASE STUDY OF ONLINE MOTORCYCLE TAXI GRABS) - Whendy Trissan; Atika Ayu Lestari (BALANGA: Jurnal Pendidikan Teknologi dan Kejuruan, 2022)
Online motorcycle taxis are application-based motorcycle taxis, since the presence of online motorcycletaxis can make it easier for people to travel using motorcycle taxis even when they don't want to leavethe house but want to buy goods, they can use online motorcycle taxi services. Likewise for onlinemotorcycle taxi drivers (Grab), they are greatly helped by Grab because it makes it easier for them toearn a living. However, not everyone realizes that joining a Grab bike partner is very profitable for them.This study was conducted to find out how much income a Grab bike partner earns.This research is a quantitative research. The sample was taken using the Stratified Random Samplingtechnique so that Grab bike Palangka Raya partners were determined to be the sample in this study. Theresearch instrument was in the form of direct interviews in order to obtain the necessary data. Then, thedata were analyzed using nonparametric statistics from Kolmogorof Smirnov Z (SPSS version 16program) and the data were normally distributed. The author finally draws conclusions based onstatistical results.The results showed that the net income of Grab bike partners was Rp. 57,938,121, - per year whichmeans that the net income for each month reaches Rp. 4.828.177,-. this is proven by the statements ofGrab bike partners when interviewed. Therefore, it can be proven that the income of Grab bikes isgreater than the Provincial Minimum Wage.